Saranrom Garden: From Siamese Royal Garden to Thailand’s Public Park - Navapan, Nattika; Noobanjong, Koompong (Journal of Architectural/Planning Research and Studies (JARS), 2022)
The opening of regal parks for public use in the West has usually been perceived as a part of a growingidea of the park as public venue. In Siam and Thailand, Saranrom Garden is one of the most obvious examplesto demonstrate the aforementioned change in land uses. It was transformed from the monarchy’s recreationalground to a seat of state agency and eventually to a public space. The investigation on the history of SaranromGarden reveals how the concept and practice of public parks came into existence in a non-Western culturewithout a direct colonization from the West.In addition, the analytical and critical readings on the development and utilization of the park arguesthat Saranrom Garden: 1) was employed by the ruling elites as an instrument to represent a modern society;and 2) functioned in terms of a hegemonic discourse, whose accessibility to the public resulted from an imitationof Western practice to display the “civilized” identity of the elites rather than from a genuine concern to producea social “release valve.”